Strengthening Legal Governance and Partnerships for Sustainable Tourism Villages Based on SDGS in Bongan Village, Tabanan - I Dewa Agung Gede Mahardika Martha; I Nyoman Sutama; Gde Deny Larasdiputra (Community Service Journal of Law, 2025)
This community service aims to strengthen legal governance and establish a multi-stakeholder partnership in managing Bongan Tourism Village, Tabanan, Bali. The program included focus group discussions (FGDs), legal and entrepreneurship training, and drafting a Memorandum of Understanding (MoU) among local institutions. The results show the preparation of a village regulation draft, increased community capacity, and a transparent partnership model. This program contributes to achieving SDG 8, 11, and 17